Personaliti remaja dalam penulisan blog - Mohd Shahremy Ikmal, Shahbudin (2018)
Past studies have shown that teenagers have different personality styles while communicating face-to-face and in writing. The difference in communication styles of these two mediums result in individual personalities having their true selves difficult to be recognized, especially in writing. The personality that exists through writing causes individuals to become independent and act irrationally on the Internet. This issue is particularly alarming, especially among teenagers in Malaysia who make up the highest number of Internet users in Malaysia. Based on the Big Five's Personality Theory, the present study was conducted to examine how teenagers communicate by using texts on the internet, in terms of: a) personality traits of all blog posts written by teenagers in 2012; b) language use in blog postings for each personality trait; and c) factors affecting personality traits in blog posts. The informants in the study consisted of two teenagers. They were screened out of 40 teenagers, aged between 16 and 19, who were active in blogging on the internet, having written 55 blog posts throughout 2012. Every blog post created throughout the year 2012 is then classified by the use of words in its text. The use of words in the text is then adjusted to the five personality traits to show the factors that influence them.The findings showed that emotion is the main factor which influenced the teenagers' personality traits in writing on the internet. The analysis of the blog posts showed the occurrences of all the five personality traits of the Big Five's Personality Theory which are Extraversion, Openness, Agreeableness, Conscientiousness and Neuroticism. In conclusion. this study has been able to assess teenagers' personality traits in blog writing compared to face-to-face. Besides, this study helps to identify teenagers' personality via blog writing and characteristics based on the five traits in the Big Five's Personality Theory.